2014
DOI: 10.1002/qua.24666
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of S(3P) + HD reaction on 13A″state and their quantum wavepacket calculation

Abstract: The time-dependent wavepacket method is used to study the reaction dynamics of S( 3 P) 1 HD (v 5 0, 1, 2) on the adiabatic 1 3 A 00 potential energy surface constructed by Han and coworkers [J. Chem. Phys. 2012, 136, 094308]. The reaction probabilities and integral cross sections as a function of collision energy are obtained and discussed. The results calculated by using the CC and the CS approximation have been compared, which suggests that for this direct abstraction reaction, the cheaper CS approximation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…And for the same collision energy, the ICSs of different vibrational quantum number have little differences. As we know, the increasing of the reagent vibrational quantum number can increase the total energy of the reaction system, which can increase the ICS of He + H2+, D2+, S + HD . However, for the title reaction, the reaction has not been promoted with the reagent vibration energies increasing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And for the same collision energy, the ICSs of different vibrational quantum number have little differences. As we know, the increasing of the reagent vibrational quantum number can increase the total energy of the reaction system, which can increase the ICS of He + H2+, D2+, S + HD . However, for the title reaction, the reaction has not been promoted with the reagent vibration energies increasing.…”
Section: Resultsmentioning
confidence: 99%
“…As we all know, some reactions, such as He + H2+, N + H2, H/D + H2, S + HD/ D2 are influenced by the reactants vibrational and rotational level changing. Sahoo et al explored reactive scattering problem of the D + + H2 in various initial states, which used a coupled three‐dimensional time‐dependent wave packet formalism in hyperspherical coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can be attributed to the asymmetric location of the center‐of‐mass of the HD diatom. The crucial effect of the mass asymmetry on the dynamics properties of the A+BC reactive systems has been discussed in the literature in more detail and the basic concepts drawn from these studies can be applied to the N( 4 S)+HD reaction. The geometry of the NHD system is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent quantum wave packet scattering calculation on H + FCl also revealed the importance of the inclusion of CC in computing the total reaction probability and the integral cross section. Study on S( 3 P) + HD verified that the CS approximation is effective for the direct abstraction reaction. Very recent study on N + H 2 (HD,D 2 ) demonstrated that the cheaper CS approximation has done well for this reactive system.…”
Section: Introductionmentioning
confidence: 97%